Comparative Analysis of Biomarkers in CAD: Evaluating Homocysteine, Lipid HS-CRP, Apo A, and ADMA - Sonu Kumar Singh; Roshan Kumar Jha; Ranjit S. Ambad; Rakesh Kumar Jha (Journal of Pharmacy and Bioallied Sciences)
Introduction: Coronary artery disease (CAD), resulting from the narrowing of coronary arteries that supply oxygen to the heart, poses a significant global health challenge. Materials and Methods: To compare the levels of homocysteine, lipid profile, lipid ratios, HS-CRP, ADMA, and apolipoproteins in CAD patients with controls, this chapter analyzes risk factors, biomarkers, and clinical traits linked to coronary artery disease (CAD) through a case–control study involving 200 participants (100 CAD cases and 100 controls). The investigation focuses on demographic variables, traditional risk factors (e.g., hypertension, smoking, alcohol intake), and essential biochemical markers such as lipid profiles, homocysteine, and emerging biomarkers like HS-CRP, ADMA, and apolipoproteins (Apo A1 and Apo B). Results and Conclusion: The findings underscore the interplay between traditional and emerging risk factors in CAD progression. LDL, homocysteine, and TC/HDL ratio emerge as robust predictors of CAD risk. The regression model’s high explanatory power (R² =97.2%) validates these indicators for effective risk assessment.